Optimasi Pendinginan Mold terhadap Fenomena Solidifikasi dan Filling pada Pengecoran Aluminium AA356 - Arif, Joni (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The casting of aluminum alloy AA356 plays a strategic role in the manufacturing industry due to its lightweight, high strength, and corrosion resistance; however, the quality of the casting is highly influenced by the mold cooling mechanism, which governs the phenomena of solidification and filling. This study aims to analyze the effect of mold cooling variations on solidification time, molten metal flow patterns, and the tendency of casting defects, in order to determine the optimal cooling configuration that enhances product quality. The research employed a quantitative approach based on numerical simulation using casting analysis software, combined with a Taguchi experimental design to evaluate mold temperature, coolant flow rate, and cooling channel distance. The simulation results were analyzed using analysis of variance (ANOVA) to identify the most significant parameters, followed by a confirmation test under the optimal conditions. The findings indicate that cooling variations significantly affect filling time, temperature distribution, and porosity levels, with certain cooling configurations capable of reducing solidification defects by more than 20% compared to the standard condition.